Health system reform in chile and colombia: results and balance (2000)
In order to understand the health system reforms, factors inherent to the health sector as well as external factors that gave origin to them must be considered. The policy of the World Bank acted as a determining factor and was taken into practice in the middle of processes that increased the inequalities in Latin America. The models of Chile and Colombia are examined from this background and some of the lessons that can be drawn from these experiences for other countries are pointed out.